Metaverse Regulation Formulation In Indonesian Cyber Law - Ridwan Ridwan; Ainun Wulandari; Syamsuddin (Universitas Muhammadiyah Surakarta, 2022)
Research Purpose: The purpose of this study is to describe and understand the formulation of the Metaverse regulation for actions prohibited in the ITE Law in the concept of cyber law and to examine how the legal conditions and developments in Indonesia respond to the presence of Metaverse. Method: The research method used is a normative legal research method using several approaches, namely: 1) Conceptual approach; 2) Statute approach; and 3) Comparative approach. Findings: The findings of the study show that the condition of human civilization is currently advancing rapidly, this refers to the ease of accessing every line of life through the use of technology. To anticipate and monitor every aspect of life that occurs in the cyber realm, the concept of Cyber Law is present in ensuring legal protection for the community as technology users. The presence of metavers needs to be anticipated by designing or updating legal products that will become a reference in protecting citizens as subjects who are active in the Metavers era. Function: The function of the study is to examines the formulation of the Metaverse regulation of actions prohibited in the ITE Law in the cyber legal framework. Novelty: This research is important considering that there are no previous studies that examine the concept of cyber law in looking at the influence of the existence of Metaverse on actions prohibited in the ITE Law. In addition, considering the importance of carrying out legal protection for every activity that occurs in the Metaverse era in an effort to develop cyber law in Indonesia in the future.